Program Daurah Bahasa Arab di Pondok Pesantren Daarul Arqom Batui Kabupaten Luwuk Banggai sebagai Upaya Menyiapkan Generasi Unggul - Sirajuddin Sirajuddin; Asri Asri; Harsya Bachtiar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2021)
The purpose of the Real Work Lecture (KKN) of STIBA Makassar Force IV is to improve the skills and cottonistas santri in interpreting the contents of the Qur'an through the Arabic language recycling program at Pondok Pesantren Darul Arqom. The method of implementing this community service program begins by mapping the problems and needs of students using SOAR analysis. After the analysis process is carried out, a work program is prepared that is appropriate and needed by the santri. In addition to carrying out the Arabic language recycling program, KKN students also help teachers in carrying out Teaching and Learning Activities (KBM) in the hut. The result of this PkM is the interest in learning Arabic and the ability of santri in interpreting the content of the Qur'an is getting better.